Prevalence and risk factors of arrhythmia in Burapha Hospital patients presenting with palpitation assessed by 24-hour Holter monitoring - Koowattanatianchai, Sukrisd; Kaladee, Akaphol; Kochaiyapatana, Patchara; Chaivanit, Pechngam (Journal of Medicine and Health Sciences, 2022)
Abstract Palpitation is one of the most common cardiac symptoms frequently encountered in medical practice. Many palpitations are caused by arrhythmia, while other causes have also been observed. This study aimed to examine the prevalence rate of arrhythmia and factors affecting the occurrence of arrhythmia in patients reporting palpitations at Burapha University Hospital. A retrospective study was employed to collect historical data on the medical records of patients with palpitations at Burapha University Hospital. These patients were diagnosed using the 24-hour Holter monitoring device during the period between January 2019 to June 2021. The data was analyzed, presented as a percentage and with 95% confidence intervals (CIs). Multivariable logistic regression analysis was utilized to ascertain statistically significant factors leading to arrhythmia, and displayed by adjusted odd ratios (ORs) and 95% CIs. The results found that the prevalence of arrhythmia was 23.7% (95% CIs = 16.7-31.9). Sick sinus syndrome appeared to be the most common variant, having an observed prevalence rate of 29.0% (95% CIs = 14.2-48.0). Other prevalent variants were premature ventricular contraction and premature atrial contraction, each of which showed a prevalence rate of 19.4% (95% CIs = 7.5-37.5). In univariate analysis, it was found that patients were over 60 years old; with hypertension, gout, coronary artery disease, and chronic kidney disease; with chest x-ray scans that showed cardiomegaly; and an estimated glomerular filtration rate < 60 ml/min/1.73m2 were significantly related to arrhythmia and with a p-value < 0.05. However, the results of multivariate analysis revealed no statistically significant relationship with the occurrence of arrhythmia. In conclusion, palpitations were attributable to arrhythmia in 25% of cases. Nevertheless, no risk factors were discovered to be statistically significant when multiple logistic regression analysis was performed.